Consumers' perception toward green food consumption - Phuah, Kit Teng (2012)
Globally, the green movement and ‘going green’ are not new concepts. It started with saving trees, replanting trees and recycling 30 years ago. However, going green has gone beyond environmentalism. The business of going green is getting more and more popular since consumers are increasingly becoming aware of environmental issues and are starting to alter their purchasing behavior to a more environmentally friendly way. Consumers’ food consumption patterns are changing rapidly. Consumers become more concerned about the food they consume. They tend to consume foods that are nutritious, healthy, safe and friendly to the environment and animals. Thus the green concept is now steadily being disseminated among consumers in conjunction with sustainability and conservation of agricultural development. However, the market for green food and green products in Malaysia is still at its infancy. Green foods refer to foods that are safe to be consumed, have fine quality, are nutritious and produced under the principles of sustainable development. The objective of this study is to determine Malaysian consumers’ awareness, perception, attitudes, and intention to purchase green food. A survey was conducted in Peninsular Malaysia where one thousand three hundred and fifty five respondents were interviewed by structured questionnaires to gather information on their awareness, perception, attitudes and intention towards green food consumption and the concept of green food. The Theory of Plan Behavior (TPB) is applied in this study. A seven (7) point Likert scale from ‘Strongly Disagree’ to ‘Strongly Agree’, ‘Not at all Important’ to ‘Extremely Important’ and ‘Never True’ to ‘Always True’ were used to measure consumers’ purchasing behavior. Descriptive statistics, chisquare,factor analysis and binary logistic regression were used to analyze the data collected. The results indicate that most of the respondents are familiar with the green concept. The results also show that there are significant differences between the consumer awareness towards green concept and social demographic profile such as age, geographical area, educational level and income. Meanwhile the results indicate that green food is not only about being organic but it also encompasses the concept of food safety, health issues, environmental hazard as well as animal welfare. Thus the major factor comes from the consumers’ educational level and income level which encourage the consumers to be more aware towards green concept and foods. Based on the factor analysis, six latent factors identify the consumers’ perception towards green food consumption. These factors are consumer referents, knowledge towards green concept and food, intention, green food attribute, motivation of consumption and product price. In addition, the results of logistic regression model show that there are significant different among most of the demographic variables (education level and income level) and dependent variables (awareness towards green concept, intention to purchase green food). The results suggest that the consumers who have higher income and educational level are more likely to have higher intention towards green food consumption. Due to the increasing awareness of consumers towards food safety, health consciousness and environmental issues, marketing strategies should be developed by the government or private organizations. Marketers in green food industry should understand the culture and lifestyle of the target consumers. For example, where they do their shopping, what food products they most prefer to buy and how they get the information about food safety, health and environmental issues. This knowledge is important to identify the local marketing of green food and it can also be a guideline for the private sector by providing accurate information of the target consumers.